Peningkatan Pemahaman Mahasiswa Nasional dan Internasional tentang Praktik Community-Based Tourism melalui Seminar Internasional - Latifah, Annisa; Inne Juni Simamora, Vera; Marvel Christabella, Delissa (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Tourism villages are one of the instruments relied upon by the government to promote sustainable tourism development. However, many tourism villages still face various obstacles in achieving independence in their management. This underscores the need to improve understanding of the aspects that determine the success of tourism village development. Therefore, this community service activity was conducted to provide students and academics with an understanding of the application of a community-based tourism approach in the context of tourism village development in Indonesia. The activity took the form of an international seminar on April 8, 2026, at the Atma Jaya Catholic University of Indonesia (ATCU) BSD Campus, involving approximately 60 participants, consisting of Indonesian students, international students from the Philippines and Timor Leste, and lecturers from both Indonesia and the Philippines. The methods used included lectures, case study presentations, and interactive discussions. The material presented covered the concepts of sustainable tourism, community-based tourism, and a comparison of case studies of Sade Village and Bilebante Village in Lombok. The activity demonstrated high participant participation in discussions regarding the success factors and challenges of tourism village management. Through the case studies presented, participants gained an understanding that community participation, clear governance, and collaboration with various stakeholders are crucial factors in realizing independent and sustainable tourism villages. This activity demonstrates that the use of real-life case studies can be an effective learning tool in introducing community-based tourism village management practices to both national and international participants.